2008
DOI: 10.1515/bc.2008.026
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the expression of components of the exocytotic machinery of insulin-secreting cells by microRNAs

Abstract: Fine-tuning of insulin secretion from pancreatic b-cells participates in blood glucose homeostasis. Defects in this process can lead to chronic hyperglycemia and diabetes mellitus. Several proteins controlling insulin exocytosis have been identified, but the mechanisms regulating their expression remain poorly understood. Here, we show that two non-coding microRNAs, miR124a and miR96, modulate the expression of proteins involved in insulin exocytosis and affect secretion of the b-cell line MIN6B1. miR124a incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
216
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(226 citation statements)
references
References 41 publications
(83 reference statements)
6
216
1
3
Order By: Relevance
“…Previous studies have reported mir-375, mir-9, mir-124a and mir-96 to play a role in regulation of insulin secretion in rodent pancreatic beta cell lines MIN6, INS-IE and MIN6 B1 cells [1][2][3][4]; however, in this study, mir-375, mir-9, mir-124a and mir-96…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Previous studies have reported mir-375, mir-9, mir-124a and mir-96 to play a role in regulation of insulin secretion in rodent pancreatic beta cell lines MIN6, INS-IE and MIN6 B1 cells [1][2][3][4]; however, in this study, mir-375, mir-9, mir-124a and mir-96…”
Section: Discussioncontrasting
confidence: 77%
“…In recent years, miRNAs have been implicated to play a role in regulation of insulin secretion [1][2][3][4], pancreatic islet development and cell differentiation [5][6][7][8][9][10][11], insulin resistance [12][13][14][15], and have been associated with secondary complications of diabetes, such as diabetic nephropathy [16,17] and cardiovascular disease [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 They negatively regulate mRNA expression by repressing translation or directly cleaving the targeted mRNA. 2 In the past few years, our understanding of the role of miRNA has expanded from the initially identified functions in the development of round worms to it becoming a highly expressed and ubiquitous regulator implicated in a wide array of critical processes, including proliferation, cell death and differentiation, 3 metabolism 4 and, importantly, tumorigenesis. 5 MiRNAs are thought to regulate about 30% of the protein-coding genes of the human genome, and individual miRNAs typically target several transcripts rather than just one specific gene.…”
Section: Micrornas and Death Receptorsmentioning
confidence: 99%